FROM INFLUENCE TO INTENTION: EXPLORING THE DRIVERS AND CONSEQUENCES OF CONSUMERS ATTITUDES TOWARDS INFLUENCER ADVERTISING (Lex localis - Journal of Local Self-Government, 2025)
The existing advertising and marketing research highlights the role of relevant antecedents of celebrity endorsements that are effective in shaping positive brand attitudes and boosting purchase intentions. However, limited attention has been given to digital influencers in this context. This study aims to fill this gap by identifying and exploring pertinent influencer attributes that form antecedents to consumer’s attitude towards influencer’s endorsements. We explore the role of digital influencers' attractiveness, expertise, trustworthiness and popularity in shaping the consumer’s attitude towards their endorsements, and its related consequences. The study tested the model using data from 501 digital influencer followers using PLS SEM. The findings reveal that influencer attractiveness is the strongest predictor of consumer’s attitude towards influencer advertising. Social media influencer’s expertise and trustworthiness also positively affect consumer’s attitude towards influencer advertising. Interestingly, the study found that the popularity of the influencer was insignificant and had no impact on consumer attitudes. Brand attitude and purchase intentions were found to be positively influenced as a consequence of consumer’s attitude towards influencer advertising. The research offers valuable theoretical insights and practical implications, which are elaborated upon in the paper.